An evaluation of the library ambience of the University of the Philippines College of Education library based on user perception - Olid, Jerwin Joshua R; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
Library ambience is significant for the efficiency in meeting the needs of the patrons and is critical in the process of planning and maintaining right atmospheric factors. This study is focused on evaluating the library ambience of the UP College of Education library by the response of its patrons.
Sixty-three student users of the U.P. College of Education library were surveyed. The respondents were asked by a survey questionnaire that contains : 1) profile of the respondents; 2) users' context on usage of library; 3) evaluation of the U.P. College of Education library; 4) assessment of the U.P. College of Education library ambience; 5) users' assessment of their moods towards the U.P. College of Education library ambience; 6) patrons' perception towards library ambience; 7) comments and suggestions on the U.P. College of Education library ambience; 8) and experts' opinion about library ambience.
Interview with experts in the field of interior design were also conducted to obtain more credible information and further recommendations. Despite the ambience brought by the traditional library design, the users still patronize the U.P. College of Education library. The U.P. College of Education library's sufficiency of lightning device, aptness of arrangement of tables and chairs, and noise level or ambient sounds gained affirmative remarks from the respondents. Yet, in contrast, the library's thermal comfort and sufficiency of cooling device acquired dissatisfactory ratings. Furthermore, the space allocation/layout of library, appeal of tables and chairs, color scheme of walls, floor, ceiling, equipment, and the space privacy of users gained neutral and average ratings from the respondents.
Overall, the U.P. College of Education library users are pleased with the present condition and ambience of the library. However, improvements through renovation of the library are recommended by several users and experts. In correspondence to the changing preferences of the users, they now prefer a more modernized library thus subsequent to a different library ambience. Such big changes in the library in terms of interior design and ambience shall benefit the library and the library users as well.
A recommended library design for a quality ambience was conceptualized and proposed based on the findings of the study.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Education Library -- Use studies; Libraries -- Space utilization -- Philippines